The small-scale urban reservoir fisheries of Lago Paranoá, Brasília, DF, Brazil - Walter, T.; Petrere Jr., M. [UNESP] (Instituto Internacional de Ecologia, 2007)
Em muitos centros urbanos, com corpos d'água apropriados, as pescarias de pequena escala são a única fonte de proteína barata para os pobres. No Lago Paranoá, localizado em Brasília, a atividade pesqueira foi estudada através de entrevistas com 53 pescadores que vivem em cidades satélites, de Março/1999 a Março/2000, em três comunidades pesqueiras. Nesse período os pescadores viviam nas cidades satélites em média há 21,7 anos (s = 9,6 anos), com famílias de 4,9 membros (s = 3,6) e 44,2% deles não possuíam instrução mínima. Entretanto, suas condições são semelhantes aquelas apontadas pelos indicadores socioeconômicos das áreas onde residem. A pesca, embora clandestina de 1966 a 2000, gerou um rendimento médio de U$ 239,00 (s = U$ 171,77). A tilápia do Nilo Oreochromis niloticus foi a principal espécie capturada (85% de um rendimento total em peso de 62,5 t). As pescarias foram realizadas em canoas a remo, individualmente ou em duplas. As artes empregadas foram a malhadeira e a tarrafa. A malhadeira foi empregada de modo ativo sob a forma de batida, onde se bate na água com um bastão para afugentar as tilápias em direção às redes. Essa estratégia foi empregada em 64,7% das pescarias, seguida pela tarrafa (31,1%) e pela malhadeira empregada passivamente (4,2%). O pescado foi vendido diretamente nas ruas e em feiras das cidades-satélite, por atravessadores ou donos de bar. As três comunidades de pescadores apresentam estratégias diferentes para pescar e comercializar o pescado. Assim há diferenças significativas em relação à essa fonte de renda, entre as comunidades.

In many cases in large urban centers, which have appropriate waterbodies, small-scale fisheries are the only source of cheap protein for the poor. In Lago Paranoá, located in Brasília, the capital city of Brazil, fishing was studied by conducting interviews with 53 fishers filling in logbooks from March, 1999 to March, 2000 in three fishing communities. The fishers come from the poorest towns around Brasília, known as satellite-towns. They have been living there on average for 21.7 years (s = 9.6 years), their families have 4.9 members (s = 3.6) on average and 44.2% do not have a basic education. However, such characteristics are similar to the socioeconomic indices of the metropolis where they live. In spite of being illegal between 1966 and 2000, fishing generated an average monthly income of U$ 239.00 (s = U$ 171.77). The Nile Tilapia Oreocrhromis niloticus is the main captured species (85% of a total number of landings in weight of 62.5 t.). Fishing is carried out in rowing boats, individually or in pairs. The fishing equipment used are gillnets and castnets. Gillnets were used actively, whereby the surface of the water is beaten with a stick to drive Tilapias towards nets as they have the ability to swim backwards. This fishing strategy was used in 64.7% of the fisheries, followed by castnets (31.1%) and by gillnets which were used less (4.2%). The fish is sold directly in the streets and fairs of the satellite-towns to middlemen or to bar owners. Three communities have different strategies in terms of fishing equipments, fishing spots and commercialization. Consequently, there are statistically significant differences in relation to the monthly income for each one of these communities.
A pesca de pequena escala no Lago Paranoá Brasília, DF, Brazil
Keywords: Pescaria continental de pequena escala; pescaria em reservatório urbano; renda proveniente da pesca; Lago Paranoá; Brasília; Brasil; Inland small-scale fishery; urban reservoir fisheries; fishing income; Lago Paranoá; Brasília; Brazil